2005
DOI: 10.1002/dev.20107
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of endogenous opioids in learned odor–stroke associations in infant rats

Abstract: Maternal touch profoundly regulates infant neural and behavioral development, and supports learned odor associations necessary for infant attachment. Endogenous opioids are well characterized to mediate the calming and analgesic properties of maternal touch; yet their role in learned odor-touch associations is unknown. We administered naltrexone, an opioid receptor antagonist, before or immediately following classical conditioning with peppermint odor and tactile stimulation (stroking) in rat neonates. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 75 publications
0
39
1
Order By: Relevance
“…Additionally, a group of pups were exposed to stroking with a soft brush in the presence of an odor CS. This procedure was designed to replicate the methods of previous investigators (e.g., Pedersen et al, 1982;Roth & Sullivan, 2006;Sullivan, Brake, Hofer, & William, 1986;Sullivan & Hall, 1988;Woo & Leon, 1987) who have reported that stroking stimulation, intended to mimic some of the mechanical effects of tactile stimulation from maternal contact such as licking, can serve as reinforcer for pups' odor learning.…”
Section: Developmental Psychobiologymentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, a group of pups were exposed to stroking with a soft brush in the presence of an odor CS. This procedure was designed to replicate the methods of previous investigators (e.g., Pedersen et al, 1982;Roth & Sullivan, 2006;Sullivan, Brake, Hofer, & William, 1986;Sullivan & Hall, 1988;Woo & Leon, 1987) who have reported that stroking stimulation, intended to mimic some of the mechanical effects of tactile stimulation from maternal contact such as licking, can serve as reinforcer for pups' odor learning.…”
Section: Developmental Psychobiologymentioning
confidence: 95%
“…Their research has linked these undefined aspects of maternal behavior to behavioral and neurological alterations in offspring development as well as to enduring, epigenetic changes in gene expression (e.g., Champagne, 2008;Champagne, Diorio, Sharma, & Meaney, 2001;Francis, Champagne, & Meaney, 2000;Liu, Diorio, Day, Francis, & Meaney, 2000;Liu et al, 1997;Meaney, 2010;Meaney & Szyf, 2005). In other studies of age-dependent odor learning in rats, stroking a pup's body with a soft brush is used to ''mimic'' maternal licking; this stimulation can lead to preferential approach toward a conditioned odor (Moriceau & Sullivan, 2005;Roth & Sullivan, 2006;Sullivan & Hall, 1988;Sullivan & Wilson, 1994;Woo & Leon, 1987). Such conditioned approach behavior is often interpreted as representing approach to the mother, reinforced by a simulation of maternal licking/grooming (e.g., Moriceau & Sullivan, 2005;Pedersen et al, 1982;Sullivan & Hall, 1988).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, in monkeys and rodents, social bonding is not possible without soft tactile stimulation from the mother (Fleming, Korsmit, & Deller, 1994;Fleming, O'Day, & Kraemer, 1999). Importantly, such stimulation serves as reward in associative conditioning to odor in rats, which was eliminated by blocking uORs (Roth & Sullivan, 2005), and soft-touch reward was associated to odor in human neonates (Sullivan, 1991). Mammals, and especially primates, have evolved particular receptors on hairy skin and a sensory pathway for soft touch Olausson et al, 2002) that projects to the anterior insular cortex, a structure that mediates awareness of the subjective experience of emotions (Craig, 2009).…”
Section: Neurobiological Genetic and Experiential Factors In Socialmentioning
confidence: 96%
“…For example, in adult rats, post conditioning administration of opioid receptor antagonists can facilitate [144][145][146], whereas post conditioning administration of opioid receptor agonists can impair memory for fear conditioning [147,148]. Rather than being underdeveloped, the endogenous opioid system is active from birth [149] and plays a role in behaviours that are important during infancy such as suckling, social play and odour preference learning [150][151][152][153][154][155][156][157][158]. One study has examined the role of opioid receptors in the retrieval of fear memories in young rats [159].…”
Section: Pharmacological Developmentmentioning
confidence: 98%